Integration of Religious Values in Character Education: Building the Morals of the Golden Generation - Jakandar, Lalu Iwan Eko; Pantiwati, Yuni; Sunaryo, Hari; Fikriah, Asfa (Al-Hayat: Journal of Islamic Education, 2025)
The integration of religious values in character education is one of the important strategies in shaping the morals and ethics of the young generation in the modern era. This study aims to examine how religious values can be integrated into character education in order to build a golden generation with noble character, integrity, and high social awareness. The method used in this study is a qualitative approach with a descriptive case study research type at SDII Muslim Madani. Researchers to dig up detailed information through observation, interviews, and documentation. The subjects of the study were the principal, teachers and students. Data analysis techniques include data reduction, data presentation, and drawing conclusions or verification. The results of this study indicate that the integration of religious values in character education takes place through habituation activities in schools including congregational prayer activities as a means of character and spiritual education, tadarus and memorization of the Qur'an as strengthening religious values, religious extracurricular activities as self-development and student potential, and alms programs as social awareness education. This study highlights how religious-based character education is not only instilled through formal teaching, but also through daily practices that shape school habits and culture. This study also provides a holistic perspective by linking religious activities with aspects of students' self-development and social development. This study may be limited to the context of a particular school with a strong religious culture, so generalization to schools with different backgrounds may be limited. In addition, the research method used is likely more qualitative, so it has not measured the specific impact of each activity on students' character development quantitatively. Further studies are needed to explore its effectiveness in the long term and in various educational settings.